Automatic Alignment of Three-Bracket Setup for Orthodontic Measurements - Leinthaler Ida; Gierling Hanna; Jäger Rudolf; Lapatki Bernd; Mayer Judith; Schmidt Falko; Peuscher Heiko (Current Directions in Biomedical Engineering)
Orthodontic tooth movement is related to application of forces and moments to individual teeth. Experimental testing of orthodontic wires helps clinicians to exert adequately dimensioned therapeutic loads. In this work, an existing experimental setup to analyze the force delivery of orthodontic wires is augmented with an algorithm that automatically finds a neutral position in which the wire transmits as little force and torque as possible; to this end, the drives of the setup are traversed to an optimal position based on measurements. The algorithm is first tested with the help of a simulation-based software-in-the-loop framework and then implemented on the real setup. Experimental results show massive time savings compared to manual alignment.